INTEGRATION OF PEER PHILOSOPHY INTO A STANDARDIZED SELF-MANAGEMENT MOBILE HEALTH INTERVENTION - Fortuna, K (Innov Aging, 2018)
Objective: Description of older certified peer specialists (aged 50+) integration of peer philosophy into the delivery of a integrated medical and psychiatric self-management intervention enhanced with mobile health for older adults with serious mental illness. Methods: Qualitative examination of peer case notes that were routinely entered on a peer care management electronic dashboard. This study included consumers with serious mental illness (N=8) with a mean age of 68.8 years (SD=4.9). Certified peer specialists (N=3) were all female and aged 55 years or older. Results: Peers entered 146 case notes on the peer care management notes dashboard. Five themes emerged including encouragement of self-determination, bio-psychosocial-spiritual framework guides practice, sharing lived experience to teach self-management skills, personalized text messages to reinforce self-management skill development, and identifying unmet needs and advocating for human rights. Conclusions: Peers unique perspectives and expertise was complemented with the standardized delivery of evidence-based intervention enhanced with mobile health.